Three species of monhysterids (Nematoda, Monhysterida) from mangrove forest of the Me Kong river estuary, Vietnam - Thanh, Nguyen Vu; Gagarin, Vladimir G. (Academia Journal of Biology, 2012)
Three new free-living nematode species of the order Monhysterida from Me Kong river estuaries of Vietnam are described. Daptonema brevisetosum sp. nov. resembles to Daptonema setosum (Bütschli, 1874), but differs from it by the relatively shorter outer labial setae, shorter spicules and shorter cervical and somatic setae. Subsphaerolaimus major sp. nov. similar to Subsphaerolaimus lamasus (Gerlach, 1956), Subsphaerolaimus gerlachi (Wieser, 1959) and Subsphaerolaimus litoralis Lorenzen, 1978, but differs from them by the longer body, longer spicules and presence of dorso-caudal apophysis of gubernaculum. Daptonema hirtum (Gerlach, 1957) is restored from synonymy of Daptonema setosum (Bütschli, 1874) and it is raised to range of valid species.